Fluorometric and Colorimetric Biosensors for the Assay of Cholinesterase Inhibitors - Miroslav Pohanka (Sensors)
Cholinesterases, specifically acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), play critical roles in neurotransmission and are key targets for inhibitors with therapeutic and toxicological significance. This review focuses on the development and application of fluorometric and colorimetric biosensors for the detection of cholinesterase inhibitors. These biosensors take advantage of the unique properties of AChE and BChE to provide sensitive and selective detection methods essential for environmental monitoring, food safety, and clinical diagnostics. Recent advances in assay techniques, including the use of gold nanoparticles, pseudoperoxidase nanomaterials, and innovative enzyme–substrate interactions, are highlighted. This review also discusses challenges and future directions for optimizing these biosensors for practical applications, emphasizing their potential to enhance public health and safety.